TINGKAT PENGETAHUAN DAN SIKAP MASYARAKAT DI DESA PASAR VI KUALANAMU TENTANG KESEHATAN REPRODUKSI REMAJA BERDASARKAN KEIKUTSERTAAN PADA KEGIATAN SOSIALISASI - Riri Safitri (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2020)
Adolescence is a transition period from childhood to adulthood, some adolescents do not know and understand about reproductive health, for example about menstruation and the occurrence of pregnancy. By participating in reproductive health socialization activities, it can increase knowledge about reproductive health. So research is needed on the level of knowledge and attitudes of the community in Pasar VI Kualanamu Village, Beringin District, regarding reproductive health based on participation in socialization activities. The purpose of this study was to determine differences in the level of knowledge and attitudes of the community in Pasar VI Kualanamu Village, Beringin District regarding Reproductive health based on participation in the socialization activities. And aims to determine the success of the dissemination of reproductive health carried out in the village market VI Kualanamu District Banyan. This research is a comparative study with a cross sectional approach. The research sample was taken by accidental sampling technique with a total of 64 respondents. This research was conducted in January 2020 in Pasar VI Village Kualanamu, Beringin District. The instruments used were questionnaire characteristics of respondents, questionnaires about knowledge of reproductive health, and attitudes about reproductive health health. The data analysis technique used in this study was the Mann Whitney U test. the results of this study show that respondents who participated in socialization (counseling) about reproductive health gained better knowledge about reproductive health. Furthermore, the attitudes of respondents about reproductive health in the groups that participated in the socialization had sufficient to very good attitudes, while the attitudes of respondents in the groups who did not participate in the socialization had an attitude that was not good enough to the point. The results of the analysis of the use of the Mann Whitney U test are that there is no significant difference in the level of knowledge and attitudes in the groups participating in the socialization and groups not participating in the socialization.